The whispering wars - Moriarty, Jaclyn (Arthur A. Levine Books, 2019)
In the town of Spindrift, where magical creatures frequent the area, children from crosstown school rivals the Orphanage School and the posh Brathelthwaite Boarding School must unite to defeat evil entities which have invaded their town, kidnapped children, and caused a mysterious flu.